Effect of smoking on alveolar bone resorption - Računica Jelena; Ivetić Vesna; Naumović Nada; Đurić Milanko (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: Periodontal disease is one of the most common diseases in adults. Although the cause of periodontal disease is bacterial infection from the dental plaque, the level of destruction of periodontal tissues depends on risk factors, and smoking is one of the most important ones. Aim: The aim of the present study was to determine the level of alveolar bone resorption in smokers. Materials and Methods: Radiographic examination of all present teeth was conducted in 30 smokers (12 men and 18 women) and 30 non-smokers (13 men and 17 women, control group), 20-60 years of age. Data on smoking habits, smoking period and the number of cigarettes a day were obtained using a questionnaire. The level of alveolar bone resorption was determined on retroalveolar X-rays, by measuring the distance from the amelo-cemental junction to the bone level on mesial and distal sides of each present tooth. Results: In smokers, significantly higher (p=0.00002) values of alveolar bone resorption (3.16 ± 2.07 mm) were found compared to the control group (1.72 ± 1.02 mm). In people who had been smoking for more than 15 years, significantly greater bone resorption was observed compared to those smoking for 15 years or less (p=0.00028). The interceptive relationship showed that smokers were at 2.98x greater risk (95% CI 1.04- 8.52) for the mean value of alveolar bone resorption of > 2 mm compared to non-smokers. Conclusion: The present results have shown that smoking increases alveolar bone resorption and that the period of smoking affects the level of resorption.